The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1990
DOI: 10.1177/030006059001800109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation with Polyunsaturated Ethyl Ester Lipids (Angiosan®) in Patients with Psoriasis and Psoriatic Arthritis

Abstract: A total of 80 patients with chronic, stable psoriasis, 34 of whom also had psoriatic arthritis, were treated with 1122 mg/day eicosapentaenoic acid ethyl ester and 756 mg/day docosahexaenoic acid ethyl ester. Before the study and after 4 and 8 weeks of treatment a Psoriatic Association scoring index (PASI) score was assessed. Before treatment the mean PASI score was 3.56, after 4 weeks 1.98 and after 8 weeks 1.24; the decrease in the score was highly significant (P less than 0.001). The degree of pruritus decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0
3

Year Published

1998
1998
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 15 publications
2
24
0
3
Order By: Relevance
“…They found a significant difference in the response shown by the group of patients treated with tacalcitol ointment along with 640 mg of omega-3 fatty acids compared to another group treated with tacalcitol ointment only [18]. Similar results were observed by Lassus et al in an open trial conducted in patients with chronic plaque psoriasis treated with 1.9 g of omega-3 fatty acids [27]. PASI 50 was achieved by 46.3% of patients in group A and 13.9% of patients in group B.…”
Section: Omówieniesupporting
confidence: 60%
See 4 more Smart Citations
“…They found a significant difference in the response shown by the group of patients treated with tacalcitol ointment along with 640 mg of omega-3 fatty acids compared to another group treated with tacalcitol ointment only [18]. Similar results were observed by Lassus et al in an open trial conducted in patients with chronic plaque psoriasis treated with 1.9 g of omega-3 fatty acids [27]. PASI 50 was achieved by 46.3% of patients in group A and 13.9% of patients in group B.…”
Section: Omówieniesupporting
confidence: 60%
“…PASI 50 was achieved by 46.3% of patients in group A and 13.9% of patients in group B. The authors observed that 16.25% of patients showed a 75% reduction in PASI score after omega-3 fatty acid supplementation, while 84.75% of patients had a moderate improvement in their PASI scores [27]. Mayser et al observed that 37% of patients achieved significant improvement in PASI scores in a double blinded trial evaluating the efficacy of intravenous omega-3 fatty acid infusions [15].…”
Section: Omówieniementioning
confidence: 94%
See 3 more Smart Citations